2016
DOI: 10.3390/molecules21030248
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Vegetable Oils for Cosmetic O/W Nanoemulsions: In Vivo Evaluation

Abstract: Oil-in-water nanoemulsions are stable systems with droplet sizes in the 20-200 nm range. The physicochemical properties of these systems may be influenced by the addition of additives. Thus, the influence of ethoxylated (EL) and acetylated lanolin (AL) addition on the droplet size, pH values, electrical conductivity and stability of nanoemulsions was investigated. Then, effect of nano-emulsions additives with EL (NE-EL) or AL (NE-AL) in hydration, oiliness and pH of the skin were evaluated. Nanoemulsion safety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 25 publications
0
32
0
3
Order By: Relevance
“…Recently, exotic vegetable oil-in-water nanoemulsions with the addition of ethoxylated and acetylated lanolin have been obtained by using a low energy EIP method. It has been shown that the lanolin derivative addition caused alterations of droplet size and conductivity of the systems, however the droplet size remained still within the nanometer range (20–200 nm) [ 26 ]. Lane et al [ 27 ] reported on flaxseed and algae nanoemulsions formulated with combinations of Tween 40 and lecithin.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, exotic vegetable oil-in-water nanoemulsions with the addition of ethoxylated and acetylated lanolin have been obtained by using a low energy EIP method. It has been shown that the lanolin derivative addition caused alterations of droplet size and conductivity of the systems, however the droplet size remained still within the nanometer range (20–200 nm) [ 26 ]. Lane et al [ 27 ] reported on flaxseed and algae nanoemulsions formulated with combinations of Tween 40 and lecithin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, methodologies such as atomic force microscopy [19,27], transmission electron microscopy [12,22,27,30], scanning electron microscopy [8,20,23], and optical microscopy [9,20] have been used as way to complement size determination and to evaluate particle morphology. Moreover, pH measurement of nanocarriers [25,30,33,34] allows assessing the compatibility of the skin to the nanocarrier.…”
Section: Nanocarrier Characterizationmentioning
confidence: 99%
“…It was confirmed that raspberry seed oil can be a well-tolerated base for cosmetics and dermocosmetics, not causing skin irritation. Research by Pereira et al [25] shows that the nano-emulsion based in plant oils (raspberry, passion fruit and peach oil) positively influences the condition of the skin, improves hydration and lubrication, without changing the pH value of the skin [24]. Oomah et al [23] report that raspberry seed oil has the ability to absorb UV radiation, thus it can be used and consequently a deficiency in the body of these acids (ω-3).…”
Section: Raspberry Seed Oilmentioning
confidence: 99%
“…Niculae et al [26] state that this oil can be used to prepare modern forms of cosmetics. It proved to be a valuable component, improving the antioxidative and photoprotective activity of the product [25]. Due to its anti-inflammatory properties, raspberry seed oil has also found applications in cosmetic and pharmaceutical preparations used to prevent gingivitis, eczema and other skin disorders [22].…”
Section: Raspberry Seed Oilmentioning
confidence: 99%